Necrotizing fasciitis of the breast: case report and brief review of literature - Ibtissam, Bellajdel; Ghizlane, Graiti; Mimouni, Ahmed; Saadi, Hanane; Taheri, Hafsa (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Necrotizing fasciitis of the breast is a rare entity, with very few cases reported in the literature. It is rapidly progressive and can lead to sepsis and multi-organ failure without prompt medical and surgical management. In this particular case, a 71-year-old diabetic female presented with primary necrotizing fasciitis affecting her right breast. Upon arrival, she was in septic shock, exhibiting noticeable breast necrosis and nipple discharge. Immediate resuscitation was administered, followed by a muscle-sparing mastectomy. A vacuum-assisted closure (VAC) device dressing was applied during the procedure, and the patient was subsequently managed in intensive care postoperatively. As of now, the patient is free from the disease, and her wound has completely healed.